1986
DOI: 10.1016/s0022-5347(17)44995-0
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Effect of Diethylstilbestrol with Low Dose Estramustine Phosphate in the Treatment of Advanced Prostatic Cancer: Final Analysis of a Phase III Trial of the European Organization for Research on Treatment of Cancer

Abstract: In a randomized phase III trial performed by the Urological Group of the European Organization for Research on Treatment of Cancer low dose estramustine phosphate (280 mg. twice daily for 8 weeks and 140 mg. twice daily thereafter) was compared to diethylstilbestrol (1 mg. 3 times daily) in patients with stages T3 to T4, M0 or M1 prostatic cancer. Of 248 patients entered 227 were evaluable for analysis: 115 received estramustine phosphate and 112 received diethylstilbestrol. The best response of the local tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(18 citation statements)
references
References 5 publications
1
17
0
Order By: Relevance
“…Treatment with medroxyprogesterone acetate gave inferior results [1]. The second study (protocol 30762) compared DES 1 mg 3 times a day with Estracyt and no difference was demonstrated between these two treatments using the same endpoints [2]. De Voogt et al [3] comparing data from both studies demonstrated that there is a definite increased risk in cardiovascular complications including death with the dose of DES that was given.…”
mentioning
confidence: 99%
“…Treatment with medroxyprogesterone acetate gave inferior results [1]. The second study (protocol 30762) compared DES 1 mg 3 times a day with Estracyt and no difference was demonstrated between these two treatments using the same endpoints [2]. De Voogt et al [3] comparing data from both studies demonstrated that there is a definite increased risk in cardiovascular complications including death with the dose of DES that was given.…”
mentioning
confidence: 99%
“…However, a marked testoster one surge cannot be prevented [3], Estramustine phos phate (ECT) is known to cause significant decrease in serum testosterone [4], as do other estrogens such as diethylstilbestrol (DES), and yet its cardiovascular compli cations are reported to be milder than those of DES [5]. We herein report our evaluation of the usefulness of ECT for preventing flare-up during LHRH analogue depot therapy.…”
Section: Methodsmentioning
confidence: 99%
“…Most (Smith et al, 1986;Pavone-Macaluso et al, 1986;Benson & Gill, 1986 [1981][1982][1983][1984][1985][1986] Type ofpatient and department 1981-82 1983-86 Average stay (days) (Table II). Table III shows the average cost per patient of a policy of initial LHRH analogue treatment followed by orchidectomy after 3, 6, 12, 24 or 36 months.…”
Section: Methodsmentioning
confidence: 99%